Social justice, poverty and race : normative and empirical points of view - Kriese, Paul, 1943-; Osborne, Randall E. (Value Inquiry Book Series, 2011)
A clear understanding of social justice requires complex rather than simple answers. It requires comfort with ambiguity rather than absolute answers. This is counter to viewing right versus wrong, just vs. unjust, or good vs. evil as dichotomies. This book provides many examples of where and how to begin to view these as continuums rather than dichotomies.